2019
DOI: 10.1063/1.5064438
|View full text |Cite
|
Sign up to set email alerts
|

The impact of wind field spatial heterogeneity and variability on short-term wind power forecast errors

Abstract: Wind power is associated with uncertainties in scheduling and dispatching to the power grid, because the availability of wind speed is unknown in advance, and precise wind power forecasts are crucial to reducing these uncertainties. However, the accuracy of the wind power prediction, which is driven by average wind speed forecasting, is influenced by the spatial variability of the wind field. In this paper, the mechanisms of how wind power prediction errors are caused by the spatial heterogeneity of wind speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…When multiple wind farms are integrated into a power system, the dependency between different wind farms has a significant impact on the reliability [42]. WPFEs at different locations cannot be assumed to be independent if they are geographically close owing to the inertia of meteorological forecasting systems [30,44]. According to the case studies based on western Denmark [34] and Ireland [39], the correlation of the WPFEs is strongly dependent on the distance between the wind farms.…”
Section: Introductionmentioning
confidence: 99%
“…When multiple wind farms are integrated into a power system, the dependency between different wind farms has a significant impact on the reliability [42]. WPFEs at different locations cannot be assumed to be independent if they are geographically close owing to the inertia of meteorological forecasting systems [30,44]. According to the case studies based on western Denmark [34] and Ireland [39], the correlation of the WPFEs is strongly dependent on the distance between the wind farms.…”
Section: Introductionmentioning
confidence: 99%
“…Because these atmospheres are subject to dramatic changes in the velocity and direction of wind, it is difficult to anticipate how the resulting wakes will form and what kind of power output should be expected. In Yang et al (2019), an analysis of the impact of spatial heterogeneity in wind farm flow is presented for a site within complex terrain. This study showed that using averaged values of wind conditions caused short-term wind power forecasting to be less accurate, due to spatial heterogeneity within the wind field and the variability of wind turbine power curves.…”
Section: Introductionmentioning
confidence: 99%
“…This method is easy to model and has strong adaptability to sample learning. It has been widely used in the wind power industry and other projects that require prediction [11]. An et al used the particle swarm optimization algorithm (PSO) to optimize the extreme learning machine (ELM) and combined them with the Adaboost integrated learning model to make a short-term prediction of wind power [12].…”
Section: Introductionmentioning
confidence: 99%